2021
DOI: 10.18240/ijo.2021.10.01
|View full text |Cite
|
Sign up to set email alerts
|

Anti-viral activity of Staphylococcus aureus lysates against herpes simplex virus type-I infection: an in vitro and in vivo study

Abstract: AIM: To investigate the effect of Staphylococcus aureus (S. aures) lysates (SALs) on herpes simplex virus type-I (HSV1) infection in human corneal epithelial (HCE) cells and in a mouse model of HSV1 keratitis. METHODS: HCE, Vero, HeLa, and BV2 cells were infected with HSV1 [HSV1 f strain, HSV1f; HSV-1-H129 with green fluorescent protein (GFP) knock-in, HSV1g]. Pre- or post-infection, SAL at various concentrations was added to the culture medium for 24h. GFP fluorescence in HSV1g or plaque formation by HSV1f we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…Pigment Epithelium Derived Factor has been shown in mice to reduce the severity of HSK[ 370 ]. An atypical presentation of presumed herpetic stromal keratitis was reportedly controlled following inoculation with Staphylococcus aureus lysates[ 371 ]. Ke et al [ 372 ] demonstrated the role of the FAK/PI3/Akt signaling pathway and MMP-2 and MMP-9 play in the development of HSK[ 372 ].…”
Section: Novel Therapeutic Approaches For Herpes Simplex Keratitis: C...mentioning
confidence: 99%
“…Pigment Epithelium Derived Factor has been shown in mice to reduce the severity of HSK[ 370 ]. An atypical presentation of presumed herpetic stromal keratitis was reportedly controlled following inoculation with Staphylococcus aureus lysates[ 371 ]. Ke et al [ 372 ] demonstrated the role of the FAK/PI3/Akt signaling pathway and MMP-2 and MMP-9 play in the development of HSK[ 372 ].…”
Section: Novel Therapeutic Approaches For Herpes Simplex Keratitis: C...mentioning
confidence: 99%